Finding Rapture in The Heart Of Darkness - Ludonarrative Game Design Beyond Agency, Choice and Freedom - Feld, Daniel (My University, 2017)
This master’s thesis explores ludic and narrative aspects of the games Bioshock and Spec Ops: The Line. Paying respects to the often dualistic nature of games being both story and game, the methodology used to analyze the primary sources will be a hybrid approach called ludonarratology. The central research question asks what kind of conjunction points between narrative and play exist and furthermore how the underlying design impacts players. By taking a closer look into the notions of agency, choice and player freedom elicited by the interactive property of games, it can be argued that Bioshock’s ludonarrative game design publicized a rather unknown dimension of player agency in video games. Furthermore I argue that the potent contextualized player involvement throughout Spec Ops: The Line can be understood as an auspicious challenge to player subjectivity and decision making based on Bioshock’s achievement. An analysis of The Line’s key moments under the aspect of agency, choice and freedom suggests that capitalizing certain ludonarrative game design events elicits stimulating experiences and creates opportunities for compelling interactive engagements. The research will find that play and story paired with specific designs can go beyond a simplistic state to offer distinguished and outstanding experiences in digital worlds.